Secular and spiritual gratitude writing exercises benefit gratitude, stress, positive mood, and spirituality - Clausen, Kendall; Denhartog, Jalen; Snow, Tobias; Toussaint, Loren (Forum Pedagogiczne, 2024)
This study examined the hypothesis that writing a secularly- or spiritually-oriented gratitude letter would show benefits for levels of gratitude, stress, mood, and spirituality. Participants (N = 57) wrote a secular or spiritual gratitude letter or wrote about food they ate that day (control condition). Results largely confirmed the hypotheses. Gratitude, positive affect, and spirituality were all enhanced because of either letter-writing exercise. Spiritual gratitude letter writing, however, did not preferentially enhance spirituality, as compared to secular gratitude letter writing. Only secular gratitude letter writing reduced stress levels, as compared to the control group. No group differences were observed on negative affect. Both spiritually- and secularly-based gratitude exercises enhanced gratitude, positive affect, and spirituality. Consequently, tailoring gratitude interventions to suit an individual’s spiritual or secular orientations does not differentially impact outcomes. Practitioners of gratitude for wellness, mood uplift, and spirituality should choose their preferred methods without concern for effectiveness.